2022
DOI: 10.1007/s12264-022-00968-w
|View full text |Cite
|
Sign up to set email alerts
|

Neural Correlates of Spatial Navigation in Primate Hippocampus

Abstract: The hippocampus has been extensively implicated in spatial navigation in rodents and more recently in bats. Numerous studies have revealed that various kinds of spatial information are encoded across hippocampal regions. In contrast, investigations of spatial behavioral correlates in the primate hippocampus are scarce and have been mostly limited to head-restrained subjects during virtual navigation. However, recent advances made in freely-moving primates suggest marked differences in spatial representations f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 146 publications
0
4
0
2
Order By: Relevance
“…Slower oscillations, or irregular low-frequency components at 1-4 Hz ‘delta’ band, are more frequently correlated with spatial or associative memory effects (Goyal et al, 2020; Vivekananda et al, 2021; Watrous et al, 2013), leading to the supposition that rodent hippocampal theta is simply faster than in primates (Jacobs, 2014; Mao, 2022). If our present results were based on two distinct oscillations – the faster ‘offline’ theta and the slower ‘online/memory’ delta band – we would have predicted anti-correlations or segmentation in the power plots into sub-bands.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Slower oscillations, or irregular low-frequency components at 1-4 Hz ‘delta’ band, are more frequently correlated with spatial or associative memory effects (Goyal et al, 2020; Vivekananda et al, 2021; Watrous et al, 2013), leading to the supposition that rodent hippocampal theta is simply faster than in primates (Jacobs, 2014; Mao, 2022). If our present results were based on two distinct oscillations – the faster ‘offline’ theta and the slower ‘online/memory’ delta band – we would have predicted anti-correlations or segmentation in the power plots into sub-bands.…”
Section: Discussionmentioning
confidence: 99%
“…Although the occurrence of sharp wave ripples during quiescence is highly conserved across species (Buzsáki, 2015), its dichotomy with theta is questionable (Hussin et al, 2020; Leonard et al, 2015). This may stem from differences in how and when theta oscillations appear across phylogenetic order (Green and Arduini, 1954; Ulanovsky and Moss, 2007), particularly among primates, including humans (Courellis et al, 2019; Green and Arduini, 1954; Halgren et al, 1978; Herweg et al, 2020; Jacobs, 2014; Mao, 2022; Stewart and Fox, 1991; Talakoub et al, 2019; Tamura et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…We found that the four brain regions were significantly activated during the extinction process, which was in line with the previous study [ 41 ]. As a key region for storing spatial memory [ 67 , 68 ], the expression of c-fos in the hippocampus was also significantly higher than in the non-extinction group after the process of auditory fear conditioning and extinction. This might indicate that auditory fear extinction is a complex process that includes contextual cues during learning.…”
Section: Discussionmentioning
confidence: 99%
“…En roedores, seres humanos y primates no humanos, se ha demostrado que el sistema vestibular envía señales, directamente, desde los núcleos vestibulares hacia el hipocampo, la corteza entorrinal y otras estructuras cerebrales que han sido, claramente, identificadas como parte de la red responsable de la navegación espacial 39,40 . Esta conexión no resulta extraña, ya que se puede inferir que las señales relacionadas con el movimiento y la orientación de la cabeza en el espacio son fundamentales para desarrollar un sentido de ubicación del cuerpo en relación con el entorno, y cómo esta información es crucial para planificar rutas y comportamientos para llegar a un destino específico 40 . En línea con lo previamente mencionado, se ha observado que pacientes con vestibulopatía unilateral y, especialmente bilateral, presentan déficits conductuales en tareas de navegación espacial, así como deterioro y atrofia en regiones cerebrales de esta red, como el hipocampo 41 .…”
Section: Discussionunclassified
“…Estas áreas también desempeñan un papel importante en procesos más complejos que no dependen de aferencias sensoriales nuevas, sino de la "construcción mental" visoespacial y planificación visoespacial. Estas funciones, a su vez, alimentan las capacidades de navegación espacial 40,48 .…”
Section: Discussionunclassified